2020
DOI: 10.1101/2020.04.28.20083311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anosmia in COVID-19 patients

Abstract: Word Count 206 (of 250) 20

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 10 publications
3
70
2
Order By: Relevance
“…Indeed, a proportion of patients with hRSV-associated severe bronchiolitis can develop neurological abnormalities, such as seizures ( Kho et al, 2004 , Ng et al, 2001 , Cha et al, 2019 ), central apnea ( Kho et al, 2004 ); lethargy, ( Sweetman et al, 2005 , Kho et al, 2004 ) feeding or swallowing difficulties ( Sweetman et al, 2005 , Kho et al, 2004 ), strabismus ( Antonucci and Fanos, 2005 ), encephalopathy ( Eisenhut, 2007 , Millichap and Wainwright, 2009 , Picone et al, 2019 , Bohmwald et al, 2014 , Bohmwald et al, 2018 ), and elevated cytokines levels or increased cellularity in the cerebrospinal fluid (CSF) ( Kawashima et al, 2012 , Kho et al, 2004 , Otake et al, 2007 ). Additionally, studies in rodents have shown that hRSV can cause cognitive alterations, similarly to what has been reported for the other respiratory viruses, such as the influenza virus and SARS-CoV-2 ( Jurgens et al, 2012 , Jang et al, 2009 , Mao et al, 2020 , Meinhardt, 2020 , Moriguchi et al, 2020 , Bernard-Valnet, 2020 , Hornuss, 2020 , Rogers et al, 2020 ). These observations suggest that hRSV could alter the proper function of the CNS.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Indeed, a proportion of patients with hRSV-associated severe bronchiolitis can develop neurological abnormalities, such as seizures ( Kho et al, 2004 , Ng et al, 2001 , Cha et al, 2019 ), central apnea ( Kho et al, 2004 ); lethargy, ( Sweetman et al, 2005 , Kho et al, 2004 ) feeding or swallowing difficulties ( Sweetman et al, 2005 , Kho et al, 2004 ), strabismus ( Antonucci and Fanos, 2005 ), encephalopathy ( Eisenhut, 2007 , Millichap and Wainwright, 2009 , Picone et al, 2019 , Bohmwald et al, 2014 , Bohmwald et al, 2018 ), and elevated cytokines levels or increased cellularity in the cerebrospinal fluid (CSF) ( Kawashima et al, 2012 , Kho et al, 2004 , Otake et al, 2007 ). Additionally, studies in rodents have shown that hRSV can cause cognitive alterations, similarly to what has been reported for the other respiratory viruses, such as the influenza virus and SARS-CoV-2 ( Jurgens et al, 2012 , Jang et al, 2009 , Mao et al, 2020 , Meinhardt, 2020 , Moriguchi et al, 2020 , Bernard-Valnet, 2020 , Hornuss, 2020 , Rogers et al, 2020 ). These observations suggest that hRSV could alter the proper function of the CNS.…”
Section: Introductionsupporting
confidence: 59%
“…During inflammatory conditions, the downregulation of CD200 leads to increased activation of microglia ( Rogers et al, 2020 ). Moreover, it has been observed that the downregulation of CD200 leads to cognitive impairment ( Hornuss, 2020 ). Thus, the levels of CD200 mRNA and protein were measured in the brains of hRSV-infected mice.…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory ability was assessed by: using validated questionnaires focused on smell dysfunction, in three studies; obtaining objective information on smell impairment through standardised chemosensitive tests with odorants, in five studies; and considering both methods, in five studies (Table 3). 18,20,[24][25][26]29,32,34,37,[40][41][42][43][47][48][49][50][51][52][53][54][55][56][57][58][59] The remaining studies assessed olfactory ability through anamnestic data collection, simple surveys and/or structured, non-validated questionnaires (Table 4). 2,16,17,19,[21][22][23]27,28,30,31,33,35,36,38,39,[44][45][46]…”
Section: Resultsmentioning
confidence: 99%
“…Two categories of the MMAT were employed based on the study design to examine the methodological quality of these studies; quantitative non-randomized category for cross-sectional and case-control studies and quantitative descriptive category for case-report and case series ones. Of the 28 included studies, one (44) had a MMAT score of 100%, six (19,26,27,38,42,43) (19,29,40); and one study (31) was conducted in European and American countries jointly.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Four studies (28,29,31,33) did not report how to measure, just extracted from medical records. In three studies (26,27,42), the Sni n' Sticks screening test for smelling disorders was used to perform psychophysical olfactory evaluation. The other methods contain:…”
Section: Olfactory and Gustatory Dysfunction Measurementmentioning
confidence: 99%